E-learning system of UCOM for improving student assessment feedback in Oman higher education - Tawafak, Ragad M.; Awanis, Romli; ALSinani, Maryam (Springer, 2018)
This paper focused on the improvement of student’s assessment feedback and learning satisfaction in the higher education institutions in Oman using the Elearning system of University Communication Model (UCOM). During the study, an E-learning model was conceptualized using coursework program instruction, testing academic performance, faculty experience, and assessment method as the determinants. The aim of this work is to develop a ‘University Communication (UCOM) model for improving the student’s assessment method and evaluating their academic performance. In the first phase of this study, a systematic review of the existing literature was carried out to determine the suitable quantitative and qualitative criteria of feature selection, like student satisfaction and degree of learning. The next phase involved the generation of an E-learning model for assessing the feedback and approval processes. The final step is the design of the evaluation forms that can measure the satisfaction of the technology and enhance the assessment method. In this study, surveys were distributed to the students of Al-Buraimi University College (BUC), Oman, to assess their level of satisfaction in using a UCOM model which served as a link between them and the University. The results were tested for accuracy, reliability, and validity using smart PLS. The findings of this paper assisted positively in four of the deployed factors and approved the capability of the developed model in improving student’s assessment feedback using E-learning.